STABILITY OF WHEAT ENTRIES ACROSS YEARS AND NITROGEN RATES BY AMMI ANALYSIS - Al-Assafi, Radhi Dheyab (Diyala Agricultural Sciences Journal, 2018)
To study the stability of spring bread wheat entries across years and nitrogen rates, yield trials were conducted from 2010 to 2013 preceding by screening trail in 2009-2010 at farm of field crops, college of agriculture in Abu-Graib located in the middle of Iraq. Randomized complete block design (RCBD) with split plots arrangement in three replicates was followed. Across years, nitrogen rates occupied main plots whereas, genotypes were in subplots. Five promising genotypes of CIMMYT entries viz: 106s, 107s, 108s, 109s, 110s and local variety (abugraib-3) that were symbolized by letters G1, G2 to G6, respectively. Nitrogen rates were 25, 100, 175kg.N.ha-1. Each nitrogen rate within year was considered as an environment, so that, nine environments were generated. Statistical analysis results revealed that the percentage of genotypes variation from total was 65.6%, also, the percentage of environments and interaction sum of square from total variation was 26.1% and 8.3%, respectively. Sum of square of investigated variation of PCA1, PCA2 and PCA3 was 60.54%, 25.1% and 10.6%, respectively. The total of interaction variation investigated was 96.3%. Grain yield of environments ranged from 3.739 t.ha-1 that ranked the first to 2.801t.ha-1 that ranked the lowest. In addition, the grain yield of genotypes ranged from 3.783 t.ha-1 for G5 that ranked the first to 2.267 t.ha-1 for G1 that ranked the lowest. G4 was more stable than other genotypes; consequently, it was wide adapted and high yield over years. However, this statistical technique was a powerful tool for diagnosing the stable genotypes in grain yield across years of research. We can recommend cultivating G4 for its wide adapted and high stability.